(untitled) (Indian Journal of Nematology, 2024)
EDITORIAL BOARD (1979-81) Chief Editor - E KHAN, Nematology Divn., I. A. R. I., New Delhi Members -ABRAR M. KHAN, Botany Dept., A. M. V., Aligarh - A.R. SESHADRI, I. A. R. I., New Delhi - V M. DAS, Zoology Dept., Osmania Univ., Hyderabad - S.N. DAS, Nematology Dept., O. V. AT., Bhubaneshwar - C.V. SIVAKUMAR, Nematology Dept., T.N.A.V., Coimbatore - Q.H. BAQRl, Z. S. I., Calcutta - GOPAL SWAKUP, Nematology Divn., I. A. R. I., New Delhi